EXPLORING TOEFL TAKING STRATEGIES OF HIGH ACHIEVER STUDENTS OF ENGLISH EDUCATION DEPARTMENT: CASE STUDY AT UNIVERSITY OF MATARAM - Kun Anjani, Tik; Arifuddin; Farmasari, Santi; Amin, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to investigate the reading comprehension techniques employed by top achievers in the University of Mataram's TOEFL reading portion. Twenty English Education students with a TOEFL score of 500 or higher participated in this qualitative case study. Questionnaires and interviews were used to gather data, which was then subjected to a thematic analysis. The findings demonstrated that students used a variety of cognitive and metacognitive techniques, including previewing questions, inferring meaning, scanning, and skimming. Additionally, they displayed time management, emotional regulation, and customized techniques including anticipating responses and paraphrasing challenging language. Overall, the results show that their ability to adapt and combine several techniques in a flexible way during the test contributed to their success.